ENRICHING ENGLISH VOCABULARIES USING MOVIE SCRIPT IN READING CLASS - Khusniyah, Nurul Lailatul; Hakim, Lukman (Research And Innovation In Language Learning (RILL), 2019)
The purpose of this study is to get more in-depth implementation of movie scripts to increase vocabulary in reading classes. Vocabulary has a important role in understanding the contents of the reading text. The research method uses action research. So that, data analysis techniques use qualitative and quantitative data analysis techniques. The sample is taken as many as 25 students. The process of collecting data uses tests, observations, and interviews. The results showed that the vocabulary of students before and after using movie scripts was different. The average score of the student vocabulary test in the reading class showed a significant difference. The average of pre-test result is 56.2 and the post-test is 81.87